Emerging Media, Instability And Democracy: Examining The Granger-Causal Relationships Of 122 Countries From 1946 To 2014 - Wertz, Blake; Groshek, Jacob (AoIR Selected Papers of Internet Research, 2017)
This study attempted to extend findings in Groshek (2011), which used cross-national time-series data in sequences of Granger causality tests to examine the democratizing effects of newspaper, radio and television diffusion, by replicating the methodology while examining new media instead. Media Systems Dependency Theory (MSD) suggested that in countries with high media diffusion or high sociopolitical instability, new media diffusion would Granger cause democracy. However, no such relationships were observed when studying new media technology. These findings were interpreted to mean that new media does not have the democratizing ability that MSD Theory ascribes to traditional media diffusion.